Differential Effect of cis‐Eicosenoic Acid Positional Isomers on Adipogenesis and Lipid Accumulation in 3T3‐L1 Cells. Issue 6 (18th April 2018) - Senarath, Samanthika; Yoshinaga, Kazuaki; Nagai, Toshiharu; Yoshida, Akihiko; Beppu, Fumiaki; Gotoh, Naohiro
Abstract : Cis ‐eicosenoic acid‐rich fish oil have shown beneficial health effects toward obesity‐related metabolic dysfunctions. Six bioavailable cis ‐eicosenoic acid positional isomers ( c ‐20:1 PIs) are examined for their effects on adipogenesis and lipid accumulation using 3T3‐L1 preadipocytes. Cells are cultured using experimental ( c ‐20:1 PIs‐added, 50 µM) or control (oleic acid ( c 9‐18:1, 50 µM) or no fatty acids) medium. The treatment of c ‐20:1 PIs, significantly ( p  < 0.05) decreases the cellular triglyceride content compared to that of c 9‐18:1. Cells absorbed c ‐20:1 PIs at significantly ( p  < 0.05) different percentages and has altered the fatty acid metabolism. The c 15‐20:1 comparatively down‐regulated the transcriptional factors for adipogenesis (peroxisome proliferative‐activated receptor gamma and CCCAT enhancer binding protein alpha) and lipogenesis (sterol regulatory element binding protein‐1); thus, show comparative anti‐adipogenic and anti‐lipogenic effect. In conclusion, c ‐20:1 PIs affect differently on adipogenesis and lipid accumulation in 3T3‐L1 cells and the position of the double bond in c ‐20:1 influences on their functionality. Practical applications : The control of the adipogenesis and lipid accumulation in adipocytes via improving the composition of dietary fat is useful as a prevention measure for obesity and subsequent diseases. This study demonstrates the beneficial effect of cis ‐eicosenoic acid ( c ‐20:1) positional isomers particularly c 15‐20:1 in controlling the adipogenesis and subsequent lipid accumulation in adipocytes. Thus, food rich in 20:1 positional isomers, such as fish oil, plant seeds, and nuts are useful as functional foods for the prevention of obesity and could also use as effective weight loss supplements. The effect of cis ‐eicosenoic acid positional isomers ( c ‐20:1 PIs) on the adipogenesis and lipid accumulation is studied using 3T3‐L1 preadipocytes. Cells are cultured using experimental ( c ‐20:1 PIs‐added, 50 μM) or control (oleic acid ( c 9‐18:1, 50 μM) or no fatty acids) medium. The treatment of c ‐20:1 PIs, particularly c 15‐20:1 significantly ( p  < 0.05) decreases the cellular triglyceride content compared to that of c 9‐18:1 and subsequently reduces the lipid accumulation in cells. Abstract : The effect of cis ‐eicosenoic acid positional isomers ( c ‐20:1 PIs) on the adipogenesis and lipid accumulation is studied using 3T3‐L1 preadipocytes. Cells are cultured using experimental ( c ‐20:1 PIs‐added, 50 μM) or control (oleic acid ( c 9‐18:1, 50 μM) or no fatty acids) medium. The treatment of c ‐20:1 PIs, particularly c 15‐20:1 significantly ( p  < 0.05) decreases the cellular triglyceride content compared to that of c 9‐18:1 and subsequently reduces the lipid accumulation in cells.